2013
DOI: 10.4103/1793-5482.121685
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent lumbar disc herniation: A prospective comparative study of three surgical management procedures

Abstract: Context:The optimal surgical treatment of recurrent lumbar disc herniation is controversial.Aim:To compare prospectively the clinical outcomes of surgical treatment of recurrent lumbar disc herniation by three different methods; discectomy alone, discectomy with transforaminal lumbar interbody fusion (TLIF), and diecectomy with posterolateral fusion (PLF), regardless of the postoperative radiological findings.Study Design:This is a prospective, randomized, comparative study.Materials and Methods:This is a pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 36 publications
(77 reference statements)
5
50
0
1
Order By: Relevance
“…This incidence is in the midrange of values (13%-27%) reported in the literature concerning revision microdiscectomy via open or tubular approach. 6,18,43,48 Our reported incidence is clearly higher than in the ETD (nil) 1,14,39 and slightly higher than in MED (7.4%-12.5%). 15,24,32,43 Compared with a series of patients that were treated with open revision microdiscectomy in our clinic (data not shown), the durotomy incidence rate is not significantly higher.…”
Section: Discussionmentioning
confidence: 74%
“…This incidence is in the midrange of values (13%-27%) reported in the literature concerning revision microdiscectomy via open or tubular approach. 6,18,43,48 Our reported incidence is clearly higher than in the ETD (nil) 1,14,39 and slightly higher than in MED (7.4%-12.5%). 15,24,32,43 Compared with a series of patients that were treated with open revision microdiscectomy in our clinic (data not shown), the durotomy incidence rate is not significantly higher.…”
Section: Discussionmentioning
confidence: 74%
“…Etiopathogenesis is attributed to ceasing of annulus during operation, insufficient nucleation of nucleus pulposus, or displacement of a free fragment. Recurrence of lumbar disc herniation was reported as between 3% and 18% (9,10,11). In the present study, 37 (46.3%) of the cases were presented with recurrent LDH.…”
Section: Discussionmentioning
confidence: 99%
“…One review, rated at critically low quality, addressed the role of fusion for recurrent disc herniation . They concluded that there was no clinical advantage to the addition of fusion to repeat decompression for recurrent disc herniation; however, only one RCT ( n = 45) was used in this review.…”
Section: Other Degenerative Conditionsmentioning
confidence: 99%
“…Complications from spinal fusion surgery for low back pain are common. One moderate-quality review 4 estimated the rate of early surgical complications to be 16% (95% CI [12][13][14][15][16][17][18][19][20]. A more recent low-quality review 13 estimated that complications such as infections, thrombosis, nerve root injury by pedicle screw and major bleeding are much greater with surgery (relative risk (RR) 22.11 (95% CI 5.99-81.60).…”
Section: Low Back Pain and Degenerative Disc Diseasementioning
confidence: 99%